If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9y + -8 = -3y + 1 Reorder the terms: -8 + 9y = -3y + 1 Reorder the terms: -8 + 9y = 1 + -3y Solving -8 + 9y = 1 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. -8 + 9y + 3y = 1 + -3y + 3y Combine like terms: 9y + 3y = 12y -8 + 12y = 1 + -3y + 3y Combine like terms: -3y + 3y = 0 -8 + 12y = 1 + 0 -8 + 12y = 1 Add '8' to each side of the equation. -8 + 8 + 12y = 1 + 8 Combine like terms: -8 + 8 = 0 0 + 12y = 1 + 8 12y = 1 + 8 Combine like terms: 1 + 8 = 9 12y = 9 Divide each side by '12'. y = 0.75 Simplifying y = 0.75
| 7t-3(5+5)=54 | | 5(-x+1)=-8 | | (x-5)(3x+1)-(x-5)(5x+2)=0 | | 2+3x=3-(8-x) | | 6x=2x+2v | | 0.3x+0.4x+x=2x+0.15 | | 2sinx+5sinx+2=0 | | 13+3lnx=5 | | log(3t-2)=25 | | 7+1(a+1)-3a=5a | | ln(4x^2)^1/2 | | 2(5x+3)=5x-24 | | m/2=6-2m/m | | 3(3x-1)=-12 | | 3-49=5x | | Sin(x)=.15 | | 3/7=a/14 | | x=195cos | | x=3*cos(65) | | cos(65)=x/3 | | 3y+18=30+-1y | | c=5ab | | 3y+18=3-y | | Y=x^2+0.3 | | 8s+20=124 | | -2x+16=12 | | -3c+2b= | | 4x-12=4(2x-1) | | 9x-25=6x-34 | | -8x+29=61 | | y=-log(3)*(3x-6) | | v/3-4=1 |